A WESTERN SAINT’S DIALOGUE WITH INDIAN THEOLOGIANS - Stavig, Gopal (Journal of Dharma, 2000)
The religious philosophy of Saint Thomas Aquinas is compared with the ideas of twenty Indian thinkers who cover the period from the third century to modern times. The areas studied are: I) God’s five essential attributes which include a discussion of God as: simple and not a compound of substance and attributes; necessary being; having an existence identical with His essence; not composed of matter and form; immutable; pure act and never in a state of potency; infinite in His magnitude and power, eternal and omnipresent; one without a second; and absolutely perfected in goodness and love at the pinnacle of the hierarchy of existence. 2) Negative theology and the unknowability Of the Divine substance; knowing God through negation; and analogical predication. 3) God’s operational attributes of omniscience, a free and immutable will, and omnipotence; and His Divine providence. The Trinity, angels and the Divine Incarnation. 4) Proofs for the existence of God as an unmoved mover, first efficient cause and rational designer. 5) Creative activity through the Divine Mind and exeniplary ideas and the Word of God; the image of God; the reason for the creation prime matter, substantial form and substance; and the principal of individualization.